Direction of Trade Statistics Quarterly, December 2006. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2006)
This publication provides data on the country and area distribution of countries exports and imports as reported by themselves or by their partners. The quarterly issues cover data for the most recent six quarters and the latest year for 169 countries, and ten quarters and five years for the world and area tables.